The Importance of Emotional Intelligence for Authentic Leadership Style (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
The acceleration of the business environment often does not leave individuals sufficient amount of time and space to establish meaningful connections - especially among the manager's population. Although the emphasis is placed on the fact that people are the most valuable resource for organizations, the increasingly present superficial connections among colleagues do not support it. Therefore, in the context of the mentioned changes, it should be emphasized that it is not enough to pay attention only to the development of cognitive knowledge that an individual possesses and for which there are numerous programs for improvement; but rather to focus more on the emotions of individuals. In addition, in today's organizations emotionally intelligent leaders are needed more than ever. Their modus operandi should be the implementation of emotional intelligence model into organizations in an authentic way, creating organizations of the future. The aforementioned authenticity in incorporating an emotional intelligence model can help organizations achieve their full potential. Otherwise, elements of the emotional intelligence model represent nothing more than a manipulation tool for individuals to achieve their own goals, and the progress of the organization is fading away. For the purpose of this paper, managers and employees of various organizations in Croatia were surveyed in order to determine the level of emotional intelligence and its relationship to the style of leadership.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.